Analysis of heavy metal toxins in maternal and fetal hair. (18th April 2012) - Ruprai, C; Lindow, S; Johnson, J; Salih, A; van der Spuy, Z; Adewola, I; Cross, D
Abstract : Objective: To analyse maternal and fetal hair lead levels to assess chronic exposure. To evaluate if leaded petrol is associated with high levels of lead in the maternal and fetal hair. A series of epidemiological studies showed high levels of lead to cause permanent fetal neurological damage. Maternal and fetal hair lead levels are shown to be low in countries using unleaded petrol. But many countries, particularly African continent, are still using leaded petrol. Mother/baby pairs from centres in Nigeria, UK, Sudan and Cape Town were included in this study. Samples were taken within 3 days of delivery from the consented mothers and their babies. Lead level was analysed as per standard protocol in the same assay in Hull University by inductively coupled plasma mass spectrometry. The results are shown in the table and are variable and indicate that petrol is not the only source of lead exposure. The Maternal: Fetal ratio varies and seems protective of high levels in the mother.